2019
DOI: 10.1016/j.heliyon.2019.e02519
|View full text |Cite
|
Sign up to set email alerts
|

Unfinished agenda of the neonates in developing countries: magnitude of neonatal sepsis: systematic review and meta-analysis

Abstract: PurposeNeonatal sepsis is the major cause of mortality and morbidity globally, particularly in developing countries. Despite studies revealed the extent of neonatal sepsis in developing countries, the findings were inconclusive. Therefore, the main aim of this study was to determine the pooled prevalence of neonatal sepsis in developing countries.MethodsWe used a systematic review and Meta-analysis study method. The reviewed studies were accessed through an electronic web-based search strategy from the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 59 publications
(124 reference statements)
1
32
1
Order By: Relevance
“…Case fatality of neonatal sepsis is high and many of the surviving neonates suffer from poor long-term neurodevelopmental outcomes as a consequence of CNS involvement, septic shock, or hypoxemia secondary to severe parenchymal lung disease [8]. Bacterial pathogens such as Klebsiella pneumoniae, Staphylococcus aureus, and coagulase-negative Staphylococcus are the most common causes of neonatal sepsis in developing countries [9]. These organisms are highly resistant to commonly used antibiotics, which makes them challenging to treat [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Case fatality of neonatal sepsis is high and many of the surviving neonates suffer from poor long-term neurodevelopmental outcomes as a consequence of CNS involvement, septic shock, or hypoxemia secondary to severe parenchymal lung disease [8]. Bacterial pathogens such as Klebsiella pneumoniae, Staphylococcus aureus, and coagulase-negative Staphylococcus are the most common causes of neonatal sepsis in developing countries [9]. These organisms are highly resistant to commonly used antibiotics, which makes them challenging to treat [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The exact data of neonatal sepsis in the LMIC is limited [8][9][10][11]. Two studies from Nigeria showed a prevalence rate of 47.2 and 21.8% [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal infection is manifested by systemic signs of infection and isolation of a bacterial or other pathogen from the bloodstream [3,4]. Infection in newborn increases the risk of developing neurodevelopmental impairments such as delayed gross motor, language and cognitive skills later in pre-school life [5][6][7].…”
Section: Introductionmentioning
confidence: 99%